Chilling of Milkfish (Chanos chanos Forsk.) Using Sea Water Flake Ice and Its Quality Analysis - Ratna Ibrahim; Eko Nurcahya Dewi (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2008)
Nowadays, there are a number of fishing company owners asking about the effects of using sea water flake ice to the fish quality because the research results on sea water flake ice characteristics as well as the suitable ratio between fish and sea water flake ice not much been published. The aim of the research was to evaluate the quality of milkfish, after three days of storage with the ratio between the fish and sea water flake ice of 1:1; 1:2 and 1:3. The experiment design applied was a Completely Randomized Design with three treatments and was done in triplicate. The organoleptic quality data were tested with Friedman test. Data on TVBN and TMA value were tested with analyses of variance. The HSD test was conducted to find out the differences among of the treatments. The different ratio between milkfish and sea water flake ice during three days of storage in styrofoam box did not give any significant influence (P>0,05) to the organoleptic , TVBN and TMA value. The ranges of organoleptic, TVBN and TMA values of the products were 7.2-7.3; 16.07 – 17.28 mg N% and 5.48 – 6.52 mg N% respectively. Keywords : Chilling, sea water flake ice, milkfish ,quality.